THE IMPACT OF PARENTING PATTERNS ON THE ACHIEVEMENT OF STUDENTS OF THE FACULTY OF ISLAMIC RELIGION - Zamza Ramadhani Miftakhul Jannah; Triono Ali Mustofa (JURNAL ILMIAH EDUNOMIKA, 2024)
Getting good learning is a very meaningful part in giving birth to a generation that is ready to take over the task of building the future from the previous generation. Learning achievement is the result achieved by children in understanding tasks or topics obtained within a certain period of time. Learning is everyone's duty. The purpose of this research is to examine whether the results obtained are the same as previous studies. So, the researcher is interested in further research about "The Impact of Parenting Patterns on Student Achievement at the Faculty of Islamic Religion. By using a qualitative descriptive percentage approach. The case study involved 34 students of the Faculty of Islamic Religion from Muhammadiyah University of Surakarta and the distribution of questionnaires via the Google form. The results obtained with the educational background of parents; the different jobs of parents produce different parenting effects. In this study, the impact of parenting that stood out was authoritarian parenting with a percentage of 318.4%, and the results obtained from the impact of different parenting styles found the highest results in the category of good grades, totalling 16 (45.7%) students.